A clinical test for a newly developed direct brain cooling system for the injured brain and pattern of cortical brainwaves in cooling, non-cooling and dead brain - Yee, Ang Song (2020)
A direct brain cooling system was newly innovated purposedly to ensure direct delivery of therapeutic hypothermia at a selected constant temperature to the injured brain. The practicality, effectiveness and safety of this system were tested clinically in our initial series of fourteen patients with severe head injuries. The patients were randomized into two groups – direct brain cooling at 32°C and the control group. The patients underwent standard decompressive craniectomy. Post operatively, all of them received intracranial pressure, focal brain oxygenation, brain temperature and direct cortical brainwave monitoring. The direct brain cooling group did better in the Extended Glasgow Outcome Scale at the time of discharge and at six months after trauma. This could be due to a trend in the monitored parameters; reduction in intracranial pressure, increment in cerebral perfusion pressure, optimal brainredox regulation, near-normal brain temperature and lessening of epileptic-like brainwave activities are likely reasons for better outcomes in the cooling group. Finally, this manuscript depicts interesting cortical brainwaves during a transition time of being alive to dead. The demonstrated cortical brainwaves are thought as obeying the principles in quantum physics.